Pengaruh Penerapan Program Pemutihan Pajak, Pembebasan Bea Balik Nama, dan Motivasi Wajib Pajak terhadap Kepatuhan Membayar Pajak Kendaraan Bermotor di Kabupaten Mojokerto - Rani Andri Ani; Nur Ainiyah; Muhammad Bahril Ilmiddaviq (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to examine the effect of the implementation of the motor vehicle tax amnesty program, exemption from motor vehicle transfer fees, and taxpayer motivation on compliance in paying motor vehicle tax in Mojokerto Regency. The population in this study were taxpayers adjusted to the number of two-wheeled vehicles in Mojokerto Regency, which was 457,325, the sample in this study used the accidental sampling method, namely random sampling with consideration of ease of access that could be reached by researchers, namely 75 respondents with data obtained through the distribution of questionnaires online and offline. Data analysis in this study used multiple linear regression analysis with the help of SPSS version 22. The results obtained in this study were that the implementation of the tax amnesty program had a significant effect on compliance, exemption from transfer fees did not affect compliance, taxpayer motivation had a significant effect on compliance, and simultaneously all independent variables affected the dependent variable.